Searching for neutrino radio flashes from the Moon with LOFAR - Buitink, Stijn; Corstanje, Arthur; Enriquez, Emilio; Falcke, Heino; Frieswijk, Wilfred; Hörandel, Jörg R.; Mevius, Maaijke; Nelles, Anna; Thoudam, Satyendra; Schellart, Pim; Scholten, Olaf; Veen, Sanderter; et al. (AIP Conference Proceedings, 2013)
Ultra-high-energy neutrinos and cosmic rays produce short radio flashes through the Askaryan effect when they impact on the Moon. Earthbound radio telescopes can search the Lunar surface for these signals. A new generation of lowfrequency, digital radio arrays, spearheaded by LOFAR, will allow for searches with unprecedented sensitivity. In the first stage of the NuMoon project, low-frequency observations were carried out with the Westerbork Synthesis Radio Telescope, leading to the most stringent limit on the cosmic neutrino flux above 1023 eV. With LOFAR we will be able to reach a sensitivity of over an order of magnitude better and to decrease the threshold energy. © 2013 AIP Publishing LLC.
CRIS-Team Scopus Importer:2023-08-15
Keywords: cosmic rays; Moon; neutrinos; radio emission; radio telescopes